2018
DOI: 10.5604/01.3001.0010.8644
|View full text |Cite
|
Sign up to set email alerts
|

More Evidence for the Genetic Susceptibility of Mexican Population to Nonalcoholic Fatty Liver Disease through PNPLA3

Abstract: The PNPLA3 gene is associated with NAFLD in Mexican population. More studies are required to explain the high prevalence of PNPLA3 polymorphism in Mexican-Americans, Mexican-Indians, and Mexican-Mestizos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 19 publications
3
20
1
2
Order By: Relevance
“…That could potentially be explained by the deceleration of obesity rates around that time which, however, seems to have been only temporary 28. Notably, we have also found that Hispanic ethnicity was independently associated with an increased risk of NAFLD (46.0% vs 29.5% as of 2013–2016, adjusted OR of 2.7 with reference to white Americans across all study cycles; p<0.0001) which might be related to higher prevalence of unfavourable PNPLA3 genotype and, thus, greater susceptibility to NAFLD among individuals of Mexican origin 29…”
Section: Discussionmentioning
confidence: 52%
“…That could potentially be explained by the deceleration of obesity rates around that time which, however, seems to have been only temporary 28. Notably, we have also found that Hispanic ethnicity was independently associated with an increased risk of NAFLD (46.0% vs 29.5% as of 2013–2016, adjusted OR of 2.7 with reference to white Americans across all study cycles; p<0.0001) which might be related to higher prevalence of unfavourable PNPLA3 genotype and, thus, greater susceptibility to NAFLD among individuals of Mexican origin 29…”
Section: Discussionmentioning
confidence: 52%
“…In our current study, non‐Hispanic Blacks did have higher prevalence of diabetes compared to non‐Hispanic Whites; however, we did not observe the same trend amongst Mexican Americans and other Hispanics. As such, the high prevalence of NAFLD amongst Mexican Americans and other Hispanics observed in our study may be due to other genetic factors, as genetic susceptibility for NAFLD is significantly higher in those of Mexican and Hispanic descent . Adoption of American culture and lifestyle amongst Hispanics has not been found to be a risk factor for NAFLD, though this effect should be further studied as more data on other ethnic groups is released in NHANES .…”
Section: Discussionmentioning
confidence: 57%
“…Thus, a higher African genetic ancestry contribution has been found in the Brazilian population, whereas the contribution of Native American ancestry is higher in Bolivia, Peru, Mexico, Ecuador, Chile, and Colombia. Clinically, data from Mexico and Brazil have confirmed the association of the PNPLA3 rs738409 variant with NAFLD in biopsy‐proved patients.…”
Section: Factors Responsible For the Higher Prevalence Of Nafld In Lamentioning
confidence: 80%